2014
DOI: 10.1073/pnas.1317147111
|View full text |Cite
|
Sign up to set email alerts
|

A lipid-mediated conformational switch modulates the thermosensing activity of DesK

Abstract: The thermosensor DesK is a multipass transmembrane histidinekinase that allows the bacterium Bacillus subtilis to adjust the levels of unsaturated fatty acids required to optimize membrane lipid fluidity. The cytoplasmic catalytic domain of DesK behaves like a kinase at low temperature and like a phosphatase at high temperature. Temperature sensing involves a built-in instability caused by a group of hydrophilic residues located near the N terminus of the first transmembrane (TM) segment. These residues are bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…Serine residues located at the C terminus of the TMS penetrate deeper into the hydrophobic core of the membrane, which results in dehydration and repositioning of these residues to establish H-bonds with homologous serine residues on the other monomer (12). The pulling force of K10 triggered by the thickening of the membrane at low temperatures promotes the incorporation of an extra helical turn at the C terminus of the TMS (11). We propose that this reorganization involves a rotation of both the TMS and the contiguous cytoplasmic coiled-coil, which in turn results in a kinase-competent state (36).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine residues located at the C terminus of the TMS penetrate deeper into the hydrophobic core of the membrane, which results in dehydration and repositioning of these residues to establish H-bonds with homologous serine residues on the other monomer (12). The pulling force of K10 triggered by the thickening of the membrane at low temperatures promotes the incorporation of an extra helical turn at the C terminus of the TMS (11). We propose that this reorganization involves a rotation of both the TMS and the contiguous cytoplasmic coiled-coil, which in turn results in a kinase-competent state (36).…”
Section: Figmentioning
confidence: 99%
“…It has been proposed that a lysine residue (K10) located near the N terminus of the TMS and a serine zipper located at the C terminus of the TMS, which is connected to the linker region at the intracellular membrane-water interface, act together as a molecular caliper to detect changes in membrane thickness that occur as a consequence of temperature variations ( Fig. 1) (10)(11)(12). It has been reported that the thickness of lipid bilayers formed by pure synthetic phospholipids increases when temperature decreases (13,14).…”
mentioning
confidence: 99%
“…For this reason, this has been called the sunken-buoy (SB) motif (5). In addition to the SB motif, a charged linker region at the intracellular membrane-water interface was found to be important for activity (10). It has been proposed that both motifs act together as a molecular gauge that senses membrane thickness and thereby regulates the switching of activity of the intracellular catalytic domain of DesK (10).…”
Section: Significancementioning
confidence: 99%
“…In addition to the SB motif, a charged linker region at the intracellular membrane-water interface was found to be important for activity (10). It has been proposed that both motifs act together as a molecular gauge that senses membrane thickness and thereby regulates the switching of activity of the intracellular catalytic domain of DesK (10). The molecular details of the mode of action of this molecular gauge have remained elusive, however.…”
Section: Significancementioning
confidence: 99%
“…We assume that the linker in CadC transduces the signal and defines the orientation of the DNA-binding domain. Likewise a linker region in DesK, a multipass transmembrane histidine kinase of Bacillus subtilis, mediates signal transduction by adopting two conformational states[31]. The histidine kinase EnvZ also has a cytoplasmic linker of approximately 50 amino acids.…”
mentioning
confidence: 99%